2009
DOI: 10.1590/s0100-40422009000800002
|View full text |Cite
|
Sign up to set email alerts
|

Remoção de Pb2+ e Cr3+ em solução por zeólitas naturais associadas a rochas eruptivas da formação serra geral, bacia sedimentar do Paraná

Abstract: Recebido em 29/4/08; aceito em 15/4/09; publicado na web em 1/10/09 REMOVAL OF Pb 2+ AND Cr 3+ FROM AQUEOUS SOLUTION BY NATURAL ZEOLITES ASSOCIATED WITH ERUPTIVE ROCKS FROM THE SERRA GERAL FORMATION, PARANÁ SEDIMENTARY BASIN. The capacity of natural zeolites and its host rock (dacite) to remove Pb 2+ and Cr 3+ from aqueous solutions has been investigated. Results showed that both samples prefer to remove Pb 2+ instead of Cr 3+ . Almost 100% of Pb 2+ was removed from solutions with concentration until 50 mg L -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
2
0
5
Order By: Relevance
“…Shinzato et al (2009) also demonstrated that natural zeolite can be used to adsorb Cr(III) from the solution. Kiser and Manning (2010) observed that natural zeolite (faujasite) can also adsorb Cr(Untreated…”
mentioning
confidence: 94%
“…Shinzato et al (2009) also demonstrated that natural zeolite can be used to adsorb Cr(III) from the solution. Kiser and Manning (2010) observed that natural zeolite (faujasite) can also adsorb Cr(Untreated…”
mentioning
confidence: 94%
“…As isotermas experimentais são úteis para se descrever a capacidade de adsorção do sistema e facilitar a avaliação em relação ao adsorvente mais adequado como das quantidades requeridas. Além disso, as isotermas desempenham um papel importante na construção de modelos para análise e descrição do sistema de adsorção utilizado (SHINZATO et al, 2009). Gráficos envolvendo a capacidade de adsorção (q) versus concentração (C) podem ser obtidos utilizando uma massa de adsorvente e várias concentrações iniciais de adsorvato.…”
Section: Monômerosunclassified
“…Onde; KF e n são constantes da isoterma de Freundlich descrevem a capacidade de adsorção (mg g -1 ) e índice de intensidade de adsorção, Ce é a concentração de equilíbrio em solução (mg L -1 ) e qe descreve a quantidade de soluto adsorvida em (mg g -1 ) (BABEL; KURNIAWAN, 2004;SHINZATO et al, 2009).…”
Section: = + (13)unclassified
See 1 more Smart Citation
“…Segundo SHINZATO (2009), a combinação dos modelos de Langmuir e Freundlich deu origem ao modelo de Langmuir-Freundlich, também conhecido como modelo de Sips, representado pela equação 7:…”
Section: Isotermaunclassified